2018
DOI: 10.1016/j.rser.2017.06.063
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study of an offshore wind farm in the Aegean Sea, Turkey

Abstract: Some rights reserved. For more information, please see the item record link above.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 41 publications
0
29
0
1
Order By: Relevance
“…The IRR indicates the efficiency of the investment: the higher the IRR, the more attractive is the project. For a project involving a rather high‐risk level, the suggested IRR is usually 15% . Thus, to achieve a 15% IRR, the minimum levoglucosan selling price ($ kg −1 ) is 4.0, the payback time was around 7 years, and this price was profitable according to other measured parameters like gross margin, ROI, and NPV.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The IRR indicates the efficiency of the investment: the higher the IRR, the more attractive is the project. For a project involving a rather high‐risk level, the suggested IRR is usually 15% . Thus, to achieve a 15% IRR, the minimum levoglucosan selling price ($ kg −1 ) is 4.0, the payback time was around 7 years, and this price was profitable according to other measured parameters like gross margin, ROI, and NPV.…”
Section: Resultsmentioning
confidence: 99%
“…In this research, the discounted cash flow analysis is conducted by increasing the selling price of levoglucosan until the IRR is 15%. When the IRR is higher than 15%, the plant is not involved at a high risk level . This analysis required the discount rate, depreciation method, income tax rates, plant life, and construction start‐up duration to be specified.…”
Section: Methodsmentioning
confidence: 99%
“…The heavy economic burden of importing these resources and more importantly, the increasing awareness of environmental issues have been encouraging policy makers to increase the use of renewable energy sources [14]. Indeed, very detailed analyses were conducted to determine the renewable energy capacity of the country [15][16][17][18][19][20]. Within the scope of a long term project, a very important contribution to estimate the national wind power capacity was made in 2007 by the preparation of REPA database (REPA is the Turkish abbreviation for the Atlas for Wind Energy Potential of Turkey).…”
Section: Wind Energy In Turkeymentioning
confidence: 99%
“…The wind resources from the Mediterranean region were also evaluated in Balog et al [12], where a hotspot located in the vicinity of the French area was identified. In a study by Satir et al [13], several wind farm configurations that may operate in the Aegean Sea were proposed. According to these results, to develop such projects will be profitable, and even better results are expected than in the case of Germany, France, or Belgium.…”
Section: Introductionmentioning
confidence: 99%